Polymer-supported stereoselective synthesis of tetrahydro-2H-oxazolo[3,2-a]pyrazin-5(3H)-ones from N-(2-oxo-ethyl)-derivatized dipeptides via eastbound iminiums - La Venia, Agustina; Dolenský, Bohumil; Krchňák, Viktor (ACS combinatorial science, 2013)
Polymer-supported N-(2-oxo-ethyl)-derivatized Ser/Thr/Cys-containing dipeptides were synthesized and subjected to acid-mediated tandem N-acylium ion cyclization-nucleophilic addition to yield tetrahydro-2H-oxazolo[3,2-a]pyrazin-5(3H)-ones. The reaction conditions and building-block combinations for stereoselective synthesis of the newly formed asymmetric carbon were developed. The synthesis was fully compatible with solid-phase peptide synthesis, and the products serve as conformationally constrained peptidomimetics. The traceless synthesis of bicycles is also reported as part of this work.
Keywords: Polymers; Acetals; molekulární struktura; Molecular Structure; Pyrazolones; Cyclization; cyklizace; dipeptidy; stereoizomerie; Oxazoles; pyrazolony; oxazoly; polymery; Combinatorial Chemistry Techniques; Stereoisomerism; Dipeptides; techniky kombinatorické chemie; acetaly